Critical Environmental Factors in the Arctic Development Strategy - V. A. Shamakhov; A. P. Isaev; V. V. Yanovskiy (Управленческое консультирование, 2018)
The main strategic task of executive bodies of the Russian Federation is the creation of the institutional foundations for an effective Russian economy. The Russian economic interests in the Arctic are associated with colossal reserves of energy and mineral raw materials. The total cost of reconnoitered and projected resources more than $ 15 trillion. Here one-fifth of oil and near 60% of gas resources are concentrated. Also here the largest deposits of coal, gold, rare metals, a huge number of different biological resources are located. Nature and people are the two main riches of our country. Creation of conditions for preservation and effective use of these resources is the main task of the executive bodies at all levels. At the same time, the region economy effectiveness includes social and environmental security of the territory. This paper reviewed the main environmental and natural factors that are critical, to our mind, for the Arctic development.1. Permafrost and global warming, low temperatures in winter season plus very short summer are determined the specificity of any production cycle in the Arctic.2. The remoteness of the territory increases the cost of logistics of any goods and resources, as well as the road infrastructure.3. Specificity of the energy resources supply of local production and life support facilities.4. The need for institutional and legal adaptation of human resources, which are attracted to work in the Arctic, to local natural and geographical conditions in connection with the job duties performed.Our analysis allowed us to formulate a proposal for the formation of a strategy for the Arctic development by creating cluster-type support zones: a symbiosis of the territory of advanced development, a special economic zone, and a priority investment project.